Hubungan Jenis Dan Lama Penggunaan Kontrasepsi Hormonal Terhadap Gangguan Menstruasi Pada Wanita Usia Subur Di Klinik Pratama Vina Kecamatan Medan Baru Kota Medan Tahun 2023 - Asnita Sinaga; Rumondang Sitorus; Imran Surbakti; Kamelia Sinaga; Elli Tamba; Yemina Siadari (Pusat Riset dan Inovasi Nasional, 2023)
According to the World Health Organization (WHO) in 2017 contraceptive use has increased in many parts of the world, especially in Asia and Latin America and is lowest in Sub-Saharan Africa. Globally, users of modern contraception have increased significantly from 35% in 1970 to 63% in 2017. The 2019 Indonesia Health Profile data shows that most active family planning participants choose injections and pills as contraceptives and are even very dominant (more than 80 %) compared to other methods; inject (63.7%), Pill (17.0%), Implant (7.4%), IUD/IUD (7.4%), Condom (1.2%), MOW (Women's Operative Method) (2 .7%), MOP (Male Operative Method) (0.5%). (RI Ministry of Health, 2020). The side effect of hormonal contraception is disruption of menstruation. The main side effects of DMPA (Depot Medroxyprogesterone Acetate) contraception and implants are menstrual disorders in the form of amenorrhea, spotting, changes in cycles, frequency, length of menstruation and amount of blood loss. The side effects of a contraceptive method are a factor that needs to be considered in determining the decision to continue using the contraceptive method (Hartanto, 2013). The type of research used in this research is analytic with a cross sectional approach. Cross sectional is a research approach that emphasizes the time of measurement/observation of independent variable data and depends only once at a time. The research sampling technique is total sampling. This research will be conducted at the Pratama Vina Clinic, Medan Baru District, Medan City in 2023. The results of the chi-squere test d. There is a significant relationship between the type of hormonal contraception and menstrual disorders in women of childbearing age at the Pratama Vina Clinic, Medan Baru District, Medan City, in 2023 (p= 0.013) and there is a significant relationship between the length of use of hormonal contraception and menstrual disorders in women of childbearing age at the Pratama Vina Clinic, Medan Baru District, Medan City in 2023 (p=0.031).